Mapping of the Intensity of Information Technology Literacy Integration Within Geography Learning in West Java - Epon Ningrum; Iwan Setiawan; Bagja Waluya; Jalu Rafli Ismail (Universitas Pendidikan Indonesia, 2022)
Information Technology (IT) development is a circumstance that affects various aspects of life. Education in the 21st century is inseparable with the advancement of information technology, both to improve teachers' quality of teaching and exposes to students the ability to utilize information, integrate it with their knowledge, and solve problems. In regards to this, integration of information technology within scientific learning is crucial, however mapping of teachers’ information literacy has not been initiated yet. Therefore the aim of this research is to conduct study and mapping the intensity of information technology literacy integration within geography learning in West Java. The result of this study shows that teachers’ are already know what information technology is in geography learning but not yet knowing how to implement it properly in each topic or material. The gap of knowledge and practice of implementing IT in the learning process has resulted in the implementation which is only at frequent intervals even when the facility is sufficient.